Room temperature catalytic dehydrogenation of cyclic amines with the liberation of H-2 using water as a solvent - Sahoo, Manoj K.; Balaraman, Ekambaram (Green Chemistry, 2019)
Catalytic dehydrogenation of cyclic amines, in particular partially saturated N-heterocycles to N-heterocyclic arenes, with the removal of molecular hydrogen as the sole byproduct in water is reported. This dehydrogenation reaction proceeds smoothly under very mild and benign conditions and operates at room temperature. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and a newly synthesized cobalt complex as the proton-reduction catalyst. A detailed mechanistic study (control experiments, electrochemical studies, UV-visible experiments) is presented for the present dual catalysis.